A Bibliometric Analysis of Naturopathy Treatment Modalities for Diabetes Mellitus - Himel Mondal; Satyalakshmi Komarraju; D. Sathyanath; Shrikanth Muralidharan; Rintu K. Gayen (Journal of Pharmacy and Bioallied Sciences)
Diabetes mellitus (DM) continues to pose a significant global health challenge, leading to increased interest in naturopathy as a complementary therapeutic approach. This bibliometric analysis examines global research output on naturopathy in the context of DM to identify trends, collaborations, and knowledge gaps. A total of 73 publications from 1983 to 2024 were retrieved from the Web of Science database and analyzed for year-wise distribution, geographic and institutional contributions, subject areas, and publishers. The analysis revealed a notable rise in publications in 2021, with China emerging as the leading contributor, followed by South Korea and the United States. Prominent research themes included acupuncture, diabetes, and insulin resistance. Leading publishers in this field were Lippincott Williams & Wilkins, Elsevier, and Springer Nature. Despite the global rise in research, India’s participation remains limited. The study highlights the need for more evidence-based investigations to support the integration of naturopathy into mainstream diabetes management.